Potensi Insektisida Pasak Bumi (Eurycoma longifolia Jack) terhadap Hama Kubis Crocidolomia pavonana (F.) (Lepidoptera: Crambidae) - Eka Chandra Lina; Arneti Aarneti; Djoko Prijono; Dadang Dadang (Perhimpunan Entomologi Indonesia, 2009)
The research was conducted at Laboratory of Insect Physiology and Toxicology of Plant Protection Department of Bogor Agricultural University from May to July 2008. Leaves, twigs, barks, and roots of Eurycoma longifolia (Pasak bumi) were extracted with hexane, ethyl acetate, and methanol solvens. The extraction was used single method and level method. Insecticidal activity of each extract has been examined in laboratory to major cabbage pests Crocidolomia pavonana using leaf residual method. Methanol root extract from single method and level method caused 100 and 75.5% mortality of insect test respectively. Hexane and ethyl acetate extracts of leaves, twigs, and barks have low insecticidal activity. The antifeedant effect worked at insect test and varied depends on concentration level. Antifeedant effect also contributed to mortality of larvae along with toxicity of each extract.